Determinants of Work-Related Stress among Nursing Professionals - Noor, Nadia; Rehman, Saqib; Gull, Maryam (Pakistan Journal of Humanities and Social Sciences, 2023)
The work environment is one of the significant factors causing work-related stress. Supervising work-related stress is crucial as it is associated with the arousal of diseases, low productivity, and occupational calamities. This article aims to explore the concept of work-related stress and its determinant in nursing to understand this phenomenon. We used qualitative research methodology to examine work-related stress antecedents among nurses in public sector hospitals. Ten semi-structured interviews were conducted with nurses, and themes were extracted. An interpretive approach was applied for data analysis. Criticism and abuse from physicians, violence from colleagues, violence from patients, unmanageable workload, unpredictable staffing and scheduling, and gender discrimination are the primary sources of stress for nurses in public sector hospitals. Nurses experience stress ascending from the work environment's psychological, physical, and social facets. Stress reduces performance capacity, low efficiency, and lack of concern for colleagues and the organization.